Anti-Ebola virus mAb 3A6 protects highly viremic animals from fatal outcome via binding GP(1,2) in a position elevated from the virion membrane - Kathryn M. Hastie; Zhe Li Salie; Zunlong Ke; Peter J. Halfmann; Lisa Evans DeWald; Sara McArdle; Ariadna Grinyó; Edgar Davidson; Sharon L. Schendel; Chitra Hariharan; Michael J. Norris; Xiaoying Yu; et al. (Nature Communications, 2025)
Abstract Monoclonal antibodies (mAbs) against Ebola virus (EBOV) glycoprotein (GP1,2) are the standard of care for Ebola virus disease (EVD). Anti-GP1,2 mAbs targeting the stalk and membrane proximal external region (MPER) potently neutralize EBOV in vitro and are protective in a mouse model of EVD. However, their neutralization mechanism is poorly understood because they target a GP1,2 epitope that has evaded structural characterization. Using X-ray crystallography and cryo-electron tomography of mAb 3A6 complexed with its stalk–MPER epitope, we reveal a previously undescribed mechanism in which 3A6 binds to a conformation of GP1,2 that is lifted from the virion membrane. We further show that in both domestic guinea pig and rhesus monkey EVD models, 3A6 provides therapeutic benefit at high-viremia advanced disease stages and at the lowest dose yet demonstrated for any anti-EBOV mAb-based monotherapy. The findings reported here can guide design of next-generation highly potent anti-EBOV therapeutics and vaccines.